PENGARUH ALIRAN MASUK DEVISA TENAGA KERJA (WORKERS’ REMITTANCES) TERHADAP NILAI TUKAR RUPIAH - Nizar, Muhammad Afdi (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2014)
This study aims to determine the impact of workers’ remittances to the real exchange rates of rupiah during 2004 - 2013. Based on quarterly time series data and using VAR model, the results of this study suggested several conclusions : (i) the growth of remittance inflows have a positive impact on real exchange rates of rupiah. That is, the increase in remittance inflows cause the real exchange rate of the rupiah has strengthened (appreciated) in a fairly long period, i.e, up to 5 quarter, and (ii) the appreciation of the real exchange rates of rupiah just increased remittance inflows in the short term, which is about one quarter.